Semi-aromatic polyester and preparation method thereof

By introducing organic amine compounds into the polyester raw materials and adjusting the component ratio and reaction conditions of the polyester, the existing semi-aromatic polyester has solved the problems of high cost, poor thermal stability and poor impact performance, and achieved low-cost and high-performance polyester preparation.

CN119735794APending Publication Date: 2025-04-01WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411930571.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing semi-aromatic polyesters are problematic of high cost, poor thermal stability and poor impact performance, especially in the preparation process, which is too cumbersome and costly.

Method used

By introducing the organic amine compound N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine and/or 2-(2-aminoethoxy)ethanol into the polyester raw material, the component ratio and reaction conditions of the polyester are adjusted to prepare semi-aromatic polyester with low acid value, high tear performance, high heat resistance and high dart impact performance.

Benefits of technology

A low-cost, easy-to-industrial semi-aromatic polyester preparation is achieved, with significantly improved thermal stability, tearing properties and dart impact properties, while reducing acid value and extending shelf life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a semi-aromatic polyester and a preparation method thereof, the semi-aromatic polyester comprises repetitive units derived from the following components: a component A comprising: A1) at least one aliphatic dicarboxylic acid or an ester derivative thereof or an anhydride derivative thereof; a2) at least one semi-aromatic dicarboxylic acid or ester derivative thereof or anhydride derivative thereof; a component B comprising a diol having 2 to 12 carbon atoms; the component C is N, N, N ', N'-tetra (2-ethoxyl) ethylenediamine and / or 2-(2-aminoethoxyl) ethanol; wherein the content of the repetitive unit derived from the component C is 1-7000 ppm based on the total weight of the semi-aromatic polyester. Compared with the known semi-aromatic polyester, the semi-aromatic polyester provided by the invention has higher heat resistance and tear resistance, lower acid value and stronger dart falling impact performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyester synthesis, and in particular relates to a semi-aromatic polyester and a preparation method thereof. Background Art

[0002] Polybutylene terephthalate / butylene adipate copolyester (PBAT) is a long-chain aliphatic-aromatic copolyester polymer material obtained by condensing the esterification product of terephthalic acid (PTA), adipic acid (AA) and 1,4-butanediol (BDO). It is a typical semi-aromatic polyester. Polybutylene adipate terephthalate (PBAT) contains flexible aliphatic chains and rigid aromatic chains, so it has high toughness and high temperature resistance. Due to the presence of ester bonds, it is also biodegradable. It is currently one of the most active biodegradable materials in the research of biodegradable plastics and the best market application.

[0003] PBAT has good ductility and fracture toughness, excellent processability and adjustable biodegradability. It is expected to become the main alternative material for traditional plastics such as polyethylene, polypropylene and polyvinyl chloride, and has very good application prospects. At present, the cost of PBAT polyester is relatively high, and it cannot be compared with PE (polyethylene) and PP (polypropylene) in terms of price. Among the three raw materials used in the synthesis of PBAT polyester: adipic acid, terephthalic acid, and 1,4-butanediol, the high price and large amount of diols are one of the main reasons for the high price of PBAT.

[0004] PBAT polyester also faces the problem of poor thermal stability. Pure PBAT particles must be physically blended and modified with other materials through a screw extruder before they can be made into packaging bags and agricultural mulch films. Traditional PBAT polyester has poor thermal stability and is prone to varying degrees of degradation under high temperature conditions. After being made into film bags, its dart impact performance will be slightly worse than that of PE and PP.

[0005] Patent CN107778462A discloses a method for preparing thermoplastic biodegradable plastics, wherein dibasic acid and diol are subjected to esterification reaction under an inert gas environment, and then a catalyst and a stabilizer are added to obtain a product, which can obtain a biodegradable polyester with good thermal properties. However, the method described in the patent is too complicated in the polymerization process and has a high cost.

[0006] Patent CN101654511A discloses a polymerization catalytic stabilization method for polybutylene adipate-terephthalate, wherein stannous chloride and p-toluenesulfonic acid are used as dual catalysts in the synthesis process, and triphenyl phosphite is added as a stabilizer in the final polycondensation stage. This method reduces the amount of catalyst, shortens the synthesis time, and improves the thermal stability of the polyester product. However, this method uses two compounds as catalysts and a stabilizer, which is still inconvenient in practical application. In addition, chloride ions and strong acidity have a corrosive effect on equipment.

[0007] Therefore, there is an urgent need for a method for preparing heat-resistant, low-acid-value semi-aromatic polyesters that is low-cost, easy to industrialize, and has excellent comprehensive performance. Summary of the invention

[0008] In view of this, the object of the present invention is to provide a semi-aromatic polyester and a preparation method. The semi-aromatic polyester has the advantages of low acid value, high tear performance, high heat resistance and high dart impact performance by introducing organic amine compounds N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine and / or 2-(2-aminoethoxy)ethanol into the raw materials.

[0009] To achieve the above object, the present invention adopts the following technical solution:

[0010] In one aspect, the present invention provides a semi-aromatic polyester comprising repeating units derived from:

[0011] Component A, comprising:

[0012] A1) at least one aliphatic dicarboxylic acid or its ester derivative or its anhydride derivative;

[0013] A2) at least one semi-aromatic dicarboxylic acid or its ester derivative or its anhydride derivative;

[0014] Component B includes a diol having 2 to 12 carbon atoms;

[0015] Component C, N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine and / or 2-(2-aminoethoxy)ethanol;

[0016] Among them, the repeating units derived from component C are contained in an amount of 1 to 7000 ppm, based on the total weight of the semi-aromatic polyester, for example, 5 ppm, 10 ppm, 50 ppm, 100 ppm, 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm, 6000 ppm, 7000 ppm, etc., preferably 10 to 5000 ppm, and more preferably 200 to 3000 ppm.

[0017] In some specific embodiments, the N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine and 2-(2-aminoethoxy)ethanol described in component C can be used alone or as a combination of the two. Specifically, the two can be used in combination in any proportion, and preferably the mass ratio of the two is 1:0.1 to 2.

[0018] In some specific embodiments, the mass ratio of the repeating units derived from component A to the repeating units derived from component B is 1:0.5-1.5, for example, 1:0.5, 1:0.7, 1:0.9, 1:1.1, 1:1.3, 1:1.5, etc.

[0019] In some specific embodiments, based on the total molar amount of component A, the

[0020] A1) 35 to 65 mol % of at least one aliphatic dicarboxylic acid or its ester derivative or its anhydride derivative, for example 40 mol %, 45 mol %, 50 mol %, 55 mol %, 60 mol % or the like of an aliphatic dicarboxylic acid;

[0021] A2) 65 to 35 mol% of at least one semi-aromatic dicarboxylic acid or its ester derivative or its anhydride derivative; for example, 60 mol%, 55 mol%, 50 mol%, 45 mol%, 40 mol%, 35 mol% of a semi-aromatic dicarboxylic acid;

[0022] The sum of the molar percentages of component A1) and component A2) is 100%.

[0023] In some specific embodiments, in component A, the aliphatic dicarboxylic acid or its ester derivative or its anhydride derivative in component A1) is selected from one or more of succinic acid, adipic acid, sebacic acid or its ester derivative or its anhydride derivative; preferably adipic acid or its ester derivative or its anhydride derivative;

[0024] Preferably, component A1) is selected from aliphatic dicarboxylic acids, preferably one or more of succinic acid, adipic acid, sebacic acid, more preferably adipic acid.

[0025] In some specific embodiments, in component A, the semi-aromatic dicarboxylic acid or its ester derivative or its anhydride derivative in component A2) is selected from one or more of terephthalic acid or its ester derivative or its anhydride derivative;

[0026] Preferably, component A2) is selected from semi-aromatic dicarboxylic acids, preferably terephthalic acid.

[0027] In some specific embodiments, the diol having 2 to 12 carbon atoms in component B is selected from a mixture of one or more of ethylene glycol, diethylene glycol, propylene glycol, 2-methyl-1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, and 1,6-hexanediol, preferably a mixture of multiple types, and these mixtures can be combined in any proportion;

[0028] Preferably, component B is selected from a mixture of ethylene glycol and / or diethylene glycol with 1,4-butanediol and optionally propylene glycol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, more preferably a mixture of ethylene glycol and / or diethylene glycol with 1,4-butanediol.

[0029] In the present invention, the melt index of the semi-aromatic polyester is 10-100 g / min, for example, 10 g / min, 20 g / min, 30 g / min, 40 / min, 50 / min, 60 / min, 70 / min, 80 / min, 90 / min, etc., according to GB / T 3682-2000 standard, at a temperature of 190°C and a load of 12.5 kg.

[0030] In the present invention, the acid value of the semi-aromatic polyester is 5-60 mol / t, for example, 6 mol / t, 7 mol / t, 8 mol / t, 9 mol / t, 10 mol / t, 11 mol / t, 12 mol / t, 13 mol / t, 14 mol / t, 18 mol / t, 20 mol / t, 25 mol / t, 30 mol / t, 35 mol / t, 40 mol / t, 45 mol / t, 50 mol / t, 55 mol / t, 60 mol / t, etc.

[0031] In the present invention, the temperature at which the TGA thermal weight loss of the semi-aromatic polyester is 1% is 380-430° C., such as 390° C., 400° C., 410° C., 420° C., etc.

[0032] In the present invention, the dart impact performance of the semi-aromatic polyester after film blowing is 400-800g, for example, 400g, 450g, 500g, 550g, 600g, 650g, 700g, 750g, 800g, etc.

[0033] In another aspect, the present invention provides a method for preparing the aforementioned semi-aromatic polyester, comprising the following steps:

[0034] S1: mixing an aliphatic dicarboxylic acid or its ester derivative or its anhydride derivative, a diol having 2 to 12 carbon atoms and a titanate catalyst to carry out an esterification reaction to generate a first esterified product;

[0035] S2: mixing a semi-aromatic dicarboxylic acid or its ester derivative or its anhydride derivative, a diol having 2 to 12 carbon atoms and a titanate catalyst to carry out an esterification reaction to generate a second esterified product;

[0036] S3: mixing the first esterified product, the second esterified product, and N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine and / or 2-(2-aminoethoxy)ethanol to perform a diesterification reaction to obtain an esterified liquid;

[0037] S4: subjecting the esterified liquid to a condensation polymerization reaction to obtain the semi-aromatic polyester.

[0038] In some specific embodiments, the titanate catalyst in step S1 and step S2 is selected from one or more of titanium dioxide, n-butyl titanate, isopropyl titanate, tetraisopropyl titanate, tetraisobutyl titanate, titanium acetate, titanium lactate, titanium tartrate, ethylene glycol titanium, propylene glycol titanium, and butanediol titanium, more preferably n-butyl titanate.

[0039] Preferably, the amount of the catalyst in step S1 is 10 to 200 ppm of the mass of the aliphatic dicarboxylic acid or its ester derivative or its anhydride derivative, for example, 10 ppm, 20 ppm, 40 ppm, 60 ppm, 80 ppm, 100 ppm, 120 ppm, 140 ppm, 160 ppm, 180 ppm, 200 ppm, etc.;

[0040] Preferably, the amount of the catalyst in step S2 is 20 to 400 ppm of the mass of the semi-aromatic dicarboxylic acid or its ester derivative or its anhydride derivative, for example, 20 ppm, 50 ppm, 100 ppm, 150 ppm, 200 ppm, 2500 ppm, 300 ppm, 350 ppm, 400 ppm, etc.

[0041] In some specific embodiments, the diol with 2-12 carbon atoms is added twice in step S1 and step S2, and is esterified with components A1) and A2) to form an ester. Specifically, the molar ratio of the diol with 2-12 carbon atoms added in step S1 to step S2 is 0.6 to 5:1, for example, 0.6:1, 1:1, 2:1, 3:1, 4:1, 5:1, etc.; the diol with 2-12 carbon atoms in step S1 and step S2 may be the same or different;

[0042] Optionally, in step S1, the molar ratio of the aliphatic dicarboxylic acid or its ester derivative or its anhydride derivative to the diol having 2 to 12 carbon atoms is 1:1 to 6, such as 1:1.1, 1:1.5, 1:2, 1:2.5, 1:3, 1:4, 1:5, 1:6, etc., preferably 1:1 to 3;

[0043] Optionally, in step S2, the molar ratio of the semi-aromatic dicarboxylic acid or its ester derivative or its anhydride derivative to the diol having 2 to 12 carbon atoms is 1:1 to 6, for example 1:

[0044] 1, 1:2, 1:3, 1:4, 1:5, 1:6, etc., preferably 1:1-3.

[0045] In some specific embodiments, the esterification reaction in step S1 and step S2 is carried out at a temperature of 190-260°C, for example, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, etc., and for a time of 2-6h, for example, 3h, 4h, 5h, etc.

[0046] In some specific embodiments, the amount of N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine and / or 2-(2-aminoethoxy)ethanol added in step S3 is 1 to 7000 ppm, for example, 1 ppm, 5 ppm, 10 ppm, 50 ppm, 100 ppm, 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm, 6000 ppm, 7000 ppm, etc., based on the total weight of the first ester and the second ester.

[0047] In some specific embodiments, the diesterification reaction in step S3 is carried out at a temperature of 160 to 240°C, for example, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, etc., for a time of 1 to 5h, for example, 2h, 3h, 4h, 5h, etc., and the pressure is a gauge pressure of -(0 to 50) kPa.

[0048] In some specific embodiments, the polycondensation reaction in step S4 is a polycondensation reaction under two vacuum conditions, the first vacuum is to 1000-30000PaA, such as 2000PaA, 5000PaA, 10000PaA, 15000PaA, 20000PaA, 25000PaA, etc., and the reaction is continued at 235-240°C, such as 235°C, 236°C, 237°C, 238°C, 239°C, 240°C for 10-60min. , for example, 20min, 30min, 40min, 50min, etc.; the second vacuuming to less than 100PaA, for example, 90PaA, 80PaA, 70PaA, 60PaA, 50PaA, etc., isothermal reaction at 240-265°C for 60-240min, for example, isothermal reaction at 250°C or 260°C for 80min, 100min, 120min, 150min, 180min, 200min, 220min, etc.

[0049] The preparation method described above in the present invention, after the polycondensation reaction in step S4 is completed, further includes filling nitrogen into the reactor to restore it to normal pressure, extruding under nitrogen protection, cooling to room temperature and then pelletizing, and other conventional operations in the art, which are not specifically limited in the present invention.

[0050] The inventors of the present application unexpectedly discovered through research that, in the process of synthesizing copolyester, by introducing the components N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine and / or 2-(2-aminoethoxy)ethanol, a low-cost, high-heat-resistant, high-tear performance, high-dart impact and low-acid-value high-performance semi-aromatic polyester can be obtained, which greatly broadens the application field of polyester. At the same time, the content of repeating units derived from N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine and / or 2-(2-aminoethoxy)ethanol needs to be controlled. When the content is higher than 7000ppm, the semi-aromatic polyester sample will have a poor hue, the melt will produce cross-linking, and the melt strength will deteriorate. Similarly, if the content is too low, such as lower than 1ppm, the dart impact performance of the semi-aromatic polyester will be reduced, and the effect of reducing its acid value will also be poor. Therefore, based on the total weight of the semi-aromatic polyester, its content should be controlled at 1-7000 ppm, preferably 10-5000 ppm, and more preferably 200-3000 ppm. Within this range, the semi-aromatic polyester can have high thermal stability, making it more stable during processing, and will have high-strength tear resistance and dart impact resistance after being made into film bags.

[0051] Compared with the prior art, the positive effects of the present invention are:

[0052] The semi-aromatic polyester raw material of the invention contains a certain amount of N,N,N',N'-tetrakis(2-hydroxyethyl)ethylenediamine and / or 2-(2-aminoethoxy)ethanol components, which can reduce the acid value of the polyester to only 5-15 mol / t, thereby reducing the degradation rate, extending the shelf life, and improving the thermal stability of the polyester. The temperature at which the TGA thermal weight loss of the prepared semi-aromatic polyester is 1% is 380-430°C, and the processing process is more stable; the dart impact performance of the prepared semi-aromatic polyester after film blowing is 400-800g. DETAILED DESCRIPTION

[0053] The present invention is further described below in conjunction with examples. It should be noted that the examples do not limit the scope of protection claimed by the present invention, and any other known changes within the scope of rights claimed by the present invention should also be included.

[0054] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, materials and instruments in the art and can be obtained commercially:

[0055] N,N,N′,N′-Tetrakis(2-hydroxyethyl)ethylenediamine: Aladdin Reagent Co., Ltd.;

[0056] 2-(2-Aminoethoxy)ethanol: Aladdin Reagent Co., Ltd.

[0057] The basic physical properties of the semi-aromatic polyester in the embodiments of the present invention are tested by the following methods:

[0058] The test was conducted using a German GOTTFERT melt indexer-mi2, with reference to GB / T 3682-2000 standard. The test conditions were melt mass flow rate: 190°C, 12.5kg, and the melt mass flow rate (MFR) was measured.

[0059] The acid value was determined using Beijing Xuxin Instruments fully automatic acid value tester, model ST-1514: run according to the provisions of Method A in GB / T14190-2008. The mixed solvent was phenol-chloroform, with a volume ratio of 2:3. The standard titration solution was potassium hydroxide-benzyl alcohol, with a concentration of 0.01 mol / L, and the concentration of bromophenol blue indicator was 0.2%. Sample configuration: 0.5 g sample was dissolved in 25.00 mL of phenol-chloroform mixed solvent;

[0060] Shanghai HESON thermogravimetric analyzer was used. Under nitrogen protection, the sample was uniformly heated to a constant temperature of 400°C at a constant rate of (5-25)°C / min. The balance was recorded continuously. The minimum detection mass was 100 mg. The balance sensitivity was ±10 μg. The sample mass signal was recorded and displayed. The noise signal was determined by the change of temperature and noise.

[0061] The tear test is performed using the Elmender tear tester, model TMI 83-76: Cut the film according to the method specified in ISO 6383, select a suitable pendulum or weight, and the measurement reading should be within the range of 20% to 80% of the scale value. The side edges of the sample are neat, the bottom edge is completely in contact with the bottom of the clamp, and it is aligned and tightened. Without interfering with the position of the pointer, the pointer is in contact with the pointer stopper and the release position of the hem is quickly pressed for measurement.

[0062] Using C670M dart impact tester, according to the test method of GB 9639, at the beginning of the test, first select the test method, estimate an initial mass and △m value, and then conduct the test. If the first sample is broken, use the weight △m to reduce the mass of the falling body; if the first sample is not broken, the weight △m must be used to increase the mass of the falling body and conduct the test in sequence. In short, using the weight to reduce or increase the mass of the falling body depends on whether the previous sample is broken. After testing 20 samples, calculate the total number of broken samples N. If N is equal to 10, the test is completed; if N is less than 10, add samples and continue the test until N is equal to 10; if N is greater than 10, add samples and continue the test until the total number of unbroken samples is equal to 10, and finally the system automatically calculates the impact result.

[0063] Example 1

[0064] 1) Add 5 mol of adipic acid, 25 mol of ethylene glycol, and 200 ppm of tetrabutyl titanate catalyst (mass ratio of adipic acid) into a glass bottle, raise the temperature to 170° C., and take out after esterification reaction for 2 hours to generate a first esterified product.

[0065] 2) Take another glass bottle, add 5 mol of terephthalic acid, 25 mol of 1,4-butanediol, and 400 ppm of catalyst tetrabutyl titanate (based on the mass ratio of terephthalic acid), raise the temperature to 230° C., and react for 5.5 hours to generate a second esterified product.

[0066] 3) The first and second esters were added into a 5L polyester reactor, and 7000ppm N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine was added at the same time. The diesterification reaction was carried out at 235°C and a gauge pressure of -30kPa. After 2h of reaction, an esterified liquid was obtained.

[0067] 4) The reactor was gradually evacuated to 30000Pa, maintained at 235°C for 60min to carry out a pre-polycondensation reaction, and then gradually evacuated to 100Pa, heated to 265°C and maintained for a final polycondensation reaction, and reacted for 230min to obtain a polymer melt.

[0068] 5) The strands are taken out from the reactor and passed through a water tank filled with room temperature water into a pelletizer for pelletizing to obtain PBAT pellet products.

[0069] The product has a melt index of 45g / 10min, an acid value of 48mol / t, a TGA thermal weight loss temperature of 1% of 380°C, a blown film tearing performance of 3000mN, and a dart impact of 420g.

[0070] Example 2

[0071] 2) Add 5 mol of adipic acid, 17.5 mol of diethylene glycol, and 10 ppm of tetrabutyl titanate catalyst (mass ratio of adipic acid) into a glass bottle, raise the temperature to 200° C., and take out after esterification reaction for 4.5 hours to generate a first esterified product.

[0072] 2) Take another glass bottle, add 5 mol of terephthalic acid, 17.5 mol of 1,4-butanediol, and 20 ppm of catalyst tetrabutyl titanate (based on the mass ratio of terephthalic acid), raise the temperature to 225°C, and react for 4.8 hours to produce a second esterified product.

[0073] 3) The first and second esters were added into a 5L polyester reactor, and 1ppm N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine was added to carry out a diesterification reaction at 235°C and a gauge pressure of -40kPa. After 2h of reaction, an esterified liquid was obtained.

[0074] 4) The reactor was gradually evacuated to 1000 Pa, maintained at 235° C. for 50 min, and then gradually evacuated to 100 Pa, and the temperature was raised to 255° C. and maintained for a final polycondensation reaction, which lasted for 210 min to obtain a polymer melt.

[0075] 5) The strands are taken out from the reactor and passed through a water tank filled with room temperature water into a pelletizer for pelletizing to obtain PBAT pellet products.

[0076] The product has a melt index of 36g / 10min, an acid value of 25mol / t, a TGA thermal weight loss temperature of 1% of 400°C, a blown film tearing performance of 6500mN, and a dart impact of 500g.

[0077] Example 3

[0078] 1) Add 5 mol of adipic acid, 5 mol of ethylene glycol, 5 mol of diethylene glycol, and 50 ppm of tetraoctyl titanate as catalyst (mass ratio of adipic acid) into a glass bottle, raise the temperature to 225° C., and take out after esterification reaction for 2.5 hours to generate the first esterified product.

[0079] 2) Take another glass bottle, add 5 mol of terephthalic acid, 7.5 mol of 1,4-butanediol, and 100 ppm of tetraoctyl titanate as catalyst (based on the mass ratio of terephthalic acid), raise the temperature to 240° C., and perform the esterification reaction for 4 hours to generate a second esterified product.

[0080] 3) The first and second esters were added into a 5L polyester reactor, and 5000ppm N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine was added to carry out a diesterification reaction at 235°C and a gauge pressure of -35kPa. After reacting for 2h, an esterified liquid was obtained.

[0081] 4) The reactor was gradually evacuated to 2000Pa, maintained at 235°C for 20min, and then gradually evacuated to 100Pa, and the temperature was raised to 240°C and maintained for a final polycondensation reaction, which lasted for 240min to obtain a polymer melt.

[0082] 5) The strands are taken out from the reactor and passed through a water tank filled with room temperature water into a pelletizer for pelletizing to obtain PBAT pellet products.

[0083] The product has a melt index of 19g / 10min, an acid value of 16mol / t, a TGA thermal weight loss temperature of 1% of 425°C, a blow molded film tearing performance of 7000mN, and a dart impact of 700g.

[0084] Example 4

[0085] 1) Add 5 mol of adipic acid, 6 mol of ethylene glycol, 14 mol of diethylene glycol, and 20 ppm of tetraisopropyl titanate (mass ratio of adipic acid) into a glass bottle, raise the temperature to 240° C., and take out after esterification reaction for 4 hours to generate the first esterified product.

[0086] 2) Take another glass bottle, add 5 mol of terephthalic acid, 20 mol of 1,4-butanediol, and 40 ppm of tetraisopropyl titanate catalyst (based on the mass ratio of terephthalic acid), raise the temperature to 210° C., and react for 4.3 hours to generate a second esterified product.

[0087] 3) The first and second esters were added into a 5L polyester reactor and 20ppm 2-(2-aminoethoxy)ethanol was added to carry out a diesterification reaction at 235°C and a gauge pressure of -20kPa. After reacting for 2h, an esterified liquid was obtained.

[0088] 4) The reactor was gradually evacuated to 5000Pa, maintained at 237°C for 50min, and then gradually evacuated to 100Pa, and the temperature was raised to 250°C and maintained for a final polycondensation reaction, which lasted for 210min to obtain a polymer melt.

[0089] 5) The strands are taken out from the reactor and passed through a water tank filled with room temperature water into a pelletizer for pelletizing to obtain PBAT pellet products.

[0090] The product has a melt index of 47g / 10min, an acid value of 40mol / t, a TGA thermal weight loss temperature of 1% of 385°C, a blown film tearing performance of 2500mN, and a dart impact of 410g.

[0091] Example 5

[0092] 1) Add 5 mol of adipic acid, 6 mol of diethylene glycol, and 20 ppm of tetrabutyl titanate catalyst (mass ratio of adipic acid) into a glass bottle, raise the temperature to 220° C., and take out after esterification reaction for 2.2 hours to generate the first esterified product.

[0093] 2) Take another glass bottle, add 5 mol of terephthalic acid, 10 mol of 1,4-butanediol, and 100 ppm of catalyst tetrabutyl titanate (based on the mass ratio of terephthalic acid), raise the temperature to 240° C., and react for 3.5 hours to generate a second esterified product.

[0094] 3) The first and second esters were added into a 5L polyester reactor and 2500ppm N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine was added to carry out a diesterification reaction at 235°C and a gauge pressure of -40kPa. After reacting for 2h, an esterified liquid was obtained.

[0095] 4) The reactor was gradually evacuated to 1000 Pa, maintained at 237° C. for 40 min, and then gradually evacuated to 100 Pa, and the temperature was raised to 245° C. and maintained for a final polycondensation reaction for 180 min to obtain a polymer melt.

[0096] 5) The strands are taken out from the reactor and passed through a water tank filled with room temperature water into a pelletizer for pelletizing to obtain PBAT pellet products.

[0097] The product has a melt index of 18g / 10min, an acid value of 13mol / t, a TGA thermal weight loss temperature of 1% of 430°C, a blow molded film tearing performance of 8500mN, and a dart impact of 800g.

[0098] Comparative Example 1

[0099] Referring to the method of Example 1, the difference is that: in step 3), N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine is not added, and other operations and conditions remain unchanged to obtain a PBAT pellet product.

[0100] The product has a melt index of 50g / 10min, an acid value of 60mol / t, a TGA thermal weight loss temperature of 1% of 360°C, a blown film tearing property of 2000mN, and a dart impact of 260g.

[0101] Comparative Example 2

[0102] Referring to the method of Example 4, the difference is that: 2-(2-aminoethoxy)ethanol is not added in step 3), and other operations and conditions remain unchanged to obtain a PBAT pellet product.

[0103] The product has a melt index of 53 g / 10 min, an acid value of 42 mol / t, a TGA thermal weight loss temperature of 1% of 380°C, a blown film tearing property of 2300 mN, and a dart impact of 300 g.

[0104] Comparative Example 3

[0105] Referring to the method of Example 1, the difference is that in step 3), N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine is replaced with an equal amount of N,N,N′,N′-trimethylethylenediamine, and other operations and conditions remain unchanged to obtain a PBAT pellet product.

[0106] The product has a melt index of 65g / 10min, an acid value of 58mol / t, a TGA thermal weight loss temperature of 1% of 330°C, a blown film tearing property of 2700mN, and a dart impact of 220g.

[0107] Comparative Example 4

[0108] Referring to the method of Example 4, the difference is that in step 3), 2-(2-aminoethoxy)ethanol is replaced by an equal amount of 2-[2-(dimethylamino)ethoxy]ethanol, and other operations and conditions remain unchanged to obtain a PBAT pellet product.

[0109] The product has a melt index of 52g / 10min, an acid value of 68mol / t, a TGA thermal weight loss temperature of 1% of 285°C, a blown film tearing property of 2000mN, and a dart impact of 210g.

[0110] By comparing the above embodiments and comparative examples, it can be found that the preparation method of the present invention can use N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine and / or 2-(2-aminoethoxy)ethanol to modify the high dart impact performance lacking in the low-cost PBAT copolyester synthesized by partially replacing 1,4-butanediol with ethylene glycol and diethylene glycol, thereby meeting the processing and application standards of the copolyester.

[0111] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be conceived by any technician familiar with the technical field within the technical scope disclosed in the present invention should be covered within the protection scope of the present invention.

Claims

1. A semi-aromatic polyester, characterized in that Comprising repeating units derived from: Component A, comprising: A1) at least one aliphatic dicarboxylic acid or its ester derivative or its anhydride derivative; A2) at least one semi-aromatic dicarboxylic acid or its ester derivative or its anhydride derivative; Component B includes a diol having 2 to 12 carbon atoms; Component C, N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine and / or 2-(2-aminoethoxy)ethanol; The repeating units derived from component C are contained in an amount of 1 to 7000 ppm, preferably 10 to 5000 ppm, more preferably 200~3000ppm.

2. The semi-aromatic polyester according to claim 1, characterized in that The N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine and 2-(2-aminoethoxy)ethanol described in component C are used in combination in any proportion, preferably in a mass ratio of 1:0.1 to 2; and / or The mass ratio of the repeating unit derived from component A to the repeating unit derived from component B is 1:0.5-1.

5.

3. The semi-aromatic polyester according to claim 1 or 2, characterized in that Based on the total molar amount of component A, including A1) 35 to 65 mol % of at least one aliphatic dicarboxylic acid or its ester derivative or its anhydride derivative; A2) 65 to 35 mol % of at least one semi-aromatic dicarboxylic acid or its ester derivative or its anhydride derivative; The sum of the molar percentages of component A1) and component A2) is 100%.

4. The semi-aromatic polyester according to any one of claims 1 to 3, characterized in that In component A, the aliphatic dicarboxylic acid or its ester derivative or its anhydride derivative in component A1) is selected from one or more of succinic acid, adipic acid, sebacic acid or its ester derivative or its anhydride derivative; preferably adipic acid or its ester derivative or its anhydride derivative; Preferably, component A1) is selected from aliphatic dicarboxylic acids, preferably one or more of succinic acid, adipic acid, sebacic acid, more preferably adipic acid; and / or In component A, the semi-aromatic dicarboxylic acid or its ester derivative or its anhydride derivative described in component A2) is selected from one or more of terephthalic acid or its ester derivative or its anhydride derivative; Preferably, component A2) is selected from semi-aromatic dicarboxylic acids, preferably terephthalic acid.

5. The semi-aromatic polyester according to any one of claims 1 to 4, characterized in that The diol having 2 to 12 carbon atoms in component B is selected from a mixture of one or more of ethylene glycol, diethylene glycol, propylene glycol, 2-methyl-1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, and 1,6-hexanediol, preferably a mixture of multiple types, and these mixtures can be combined in any proportion; Preferably, component B is selected from a mixture of ethylene glycol and / or diethylene glycol with 1,4-butanediol and optionally propylene glycol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, more preferably a mixture of ethylene glycol and / or diethylene glycol with 1,4-butanediol.

6. The semi-aromatic polyester according to any one of claims 1 to 5, characterized in that The melt index of the semi-aromatic polyester is 10-100 g / min at a temperature of 190° C. and a load of 12.5 kg; and / or The acid value of the semi-aromatic polyester is 5-60 mol / t; and / or The temperature at which the TGA thermal weight loss of the semi-aromatic polyester reaches 1% is 380-430° C.; and / or The dart impact performance of the semi-aromatic polyester after film blowing is 400-800g.

7. A method for preparing the semi-aromatic polyester according to any one of claims 1 to 6, characterized in that: The steps include: S1: mixing an aliphatic dicarboxylic acid or its ester derivative or its anhydride derivative, a diol having 2 to 12 carbon atoms and a titanate catalyst to carry out an esterification reaction to generate a first esterified product; S2: mixing a semi-aromatic dicarboxylic acid or its ester derivative or its anhydride derivative, a diol having 2 to 12 carbon atoms and a titanate catalyst to carry out an esterification reaction to generate a second esterified product; S3: mixing the first esterified product, the second esterified product, and N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine and / or 2-(2-aminoethoxy)ethanol to perform a diesterification reaction to obtain an esterified liquid; S4: subjecting the esterified liquid to a condensation polymerization reaction to obtain the semi-aromatic polyester.

8. The preparation method according to claim 7, characterized in that: The titanate catalyst in step S1 and step S2 is selected from one or more of titanium dioxide, n-butyl titanate, isopropyl titanate, tetraisopropyl titanate, tetraisobutyl titanate, titanium acetate, titanium lactate, titanium tartrate, ethylene glycol titanium, propylene glycol titanium, butanediol titanium, more preferably n-butyl titanate; and / or The amount of the catalyst in step S1 is 10 to 200 ppm based on the mass of the aliphatic dicarboxylic acid or its ester derivative or its anhydride derivative and the diol having 2 to 12 carbon atoms; and / or The amount of the catalyst in step S2 is 20 to 400 ppm based on the mass of the semi-aromatic dicarboxylic acid or its ester derivative or its anhydride derivative and the diol having 2 to 12 carbon atoms; and / or The molar ratio of the diol having 2 to 12 carbon atoms added in step S1 to step S2 is 0.6 to 5:1; and / or In step S1, the molar ratio of the aliphatic dicarboxylic acid or its ester derivative or its anhydride derivative to the diol having 2 to 12 carbon atoms is 1:1 to 6, preferably 1:1 to 3; and / or The molar ratio of the semi-aromatic dicarboxylic acid or its ester derivative or its anhydride derivative to the diol having 2 to 12 carbon atoms in step S2 is 1:1 to 6, preferably 1:1 to 3; and / or The esterification reaction in step S1 and step S2 is carried out at a temperature of 190 to 260° C. and for a time of 2 to 6 hours.

9. The preparation method according to claim 7, characterized in that: In step S3, the amount of N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine and / or 2-(2-aminoethoxy)ethanol added is 1 to 7000 ppm of the total weight of the first esterification product and the second esterification product; and / or The diesterification reaction in step S3 is carried out at a temperature of 160 to 240° C., for 1 to 5 hours, and at a pressure of -(0 to 50) kPa.

10. The preparation method according to claim 7, characterized in that: The polycondensation reaction in step S4 is a polycondensation reaction under two vacuum conditions, the first vacuum is to 1000-30000 PaA, and the reaction is continued at 235-240°C for 10-60 minutes; the second vacuum is to less than 100 PaA, and the reaction is carried out at a constant temperature of 240-265°C for 60-240 minutes.

Citation Information

Patent Citations

  • Stable method of polymerization and catalysis of polybutylene terephthalate

    CN101654511A

  • Method for preparing thermoplastic biodegradable plastics

    CN107778462A

  • Biodegradable copolyester and preparation method thereof

    CN111848936A

  • Semi-aromatic polyether ester as well as preparation method and application thereof

    CN115806659A

  • Semi-aromatic polyester and preparation method thereof

    CN117801243A